Characterization of plasmid-mediated qnrA and qnrB genes among Enterobacteriaceae strains: quinolone resistance and ESBL production in Ismailia, Egypt - Samaa A. Taha (Egyptian Journal of Medical Human Genetics, 2019)
Abstract Background Plasmid-mediated quinolone resistance genes (PMQR) are mainly associated with clinical isolates of Enterobacteriaceae and complicate treatment of infections caused by these isolates worldwide. Extended-spectrum-beta-lactamase (ESBL)-producing bacteria are resistant to common antibiotics and also through many mechanisms, ESBL could be disabling other types of antibiotics. This study aimed to assess the prevalence of quinolone resistance and ESBL among Enterobacteriaceae strains and investigated the presence of qnrA and qnrB genes in these strains which were isolated from urinary tract infections in Ismailia, Egypt. Ninety-four Enterobacteriaceae isolates were collected from cases of UTIs admitted to the intensive care unit, Suez-Canal University Hospitals, between October 2017 and January 2018. Antibacterial susceptibility was determined by the disk diffusion method. A polymerase chain reaction assay was used to detect qnrA and qnrB resistance genes in quinolone- and fluoroquinolone-resistant and ESBL strains. Also, ciprofloxacin MIC was determined by the agar dilution method. Results Resistance rates were 59.6%, 54.3%, 53.2%, 53.2%, and 53.2% to NA, LEV, NOR, CIP, and FX, respectively. Of 56 NA-resistant isolates, 7 (12.5%) and 6 (10.7%) were positive for qnrA and qnrB, respectively, with only one isolate co-harboring both genes. ESBL-producing bacteria was 66.2% of isolates. The MICs for ciprofloxacin ranged from 32–256 μg/ml in ciprofloxacin-resistant isolates. Conclusion Our study shows high resistance rates of Enterobacteriaceae to quinolones and ESBL in our hospital which necessitate appropriate use of these antibiotics to reserve their application for therapy. The prevalence of quinolone-resistant and ESBL-producing Enterobacteriaceae was approximately 60% and 70% respectively.